A comparative study of anthropometric measurements and hypertension among geriatric patients attending OPD - G. R., Vishwanath; Sangrulkar, Tejaswini V.; S. K., Shrarma; Patil, Praveen (International Journal Of Community Medicine And Public Health, 2018)
Background: Hypertension is silent killer, its chronic condition leads to coronary heart diseases, stroke and vascular complications. It is one of the most important treatable causes of mortality and morbidity in the elderly population, the prevalence of hypertension was 40 per cent in 2008, it is estimated that by the year 2025, the majority of the elderly people worldwide will reside in developing countries. Developing countries are thus likely to face an enormous burden of vulnerable elderly population who are predisposed to chronic non‑communicable diseases. Methods: Cross-sectional study carried out in geriatric clinic of government medical college, Miraj (1st Nov-31st Dec, 2015). Results: The prevalence of hypertension among study participants was 41.46%. Prevalence of hypertension among male subjects was 56.60% where as it was 28.57% among female subjects. The body mass index was more than cut off point in hypertensive as compared to non-hypertensive in both males and females. Conclusions: The overall prevalence of hypertension in study subjects is 41%. Increased BMI and waist circumference were found in hypertensive.